The eccentric distance sum of connected graphs - Hua, Hongbo; Bao, Hongmei (Utilitas Mathematica, 2016)
The eccentric distance sum (EDS) of a connected graph G is defined as ζd(G) = Σv∈V(G) ϵG(v)DG(v), where ϵG(v) is the eccentricity of a vertex v in G and DG (v) is the sum of distances between v and all other vertices in G. In this paper, we present several new bounds for EDS in terms of other graph parameters including the Wiener index, Harary index, second multiplicative Zagreb index, multiplicative Wiener index, first Zagreb index, first Zagreb coindex, and so on. Moreover, we compare the eccentric distance sum and degree distance for some connected graphs.